Peluang dan Tantangan Gerakan Revivalisme Islam di Indonesia Pascareformasi - Gonda Yumitro (TSAQAFAH, 2018)
This article elaborates the opportunities and challenges of the Islamic revivalist movement in post-reform Indonesia since the opportunity to express the notions is opened. The issue of revivalism is not only developed in Indonesia, but also an important issue in Southeast Asia, South Asia, Middle East, and other regions. This can be seen from various studies on Islamic revivalism that occurred in various areas. Even the Islamic revivalism was actually initiated at the end of the nineteenth century by Jamaluddin al-Afghani, whose passion was continued by his disciple Muhammad Abduh. The author will explain how the challenge of the rise of Islam in Indonesia after the reformation. Therefore, the author provides a study of literature and interviews with the experts consisted of 10 people of scholars and activists of Islamic revivalism movement conducted. Based on this research, there is an indication that the Islamic revivalism movement has great opportunities and challenges in post-Indonesian reformation. Some of the opportunities for the development of Islamic revivalism movement in Indonesia are the historical factor, acculturalization through educational institutions, and the Islamization policies in some regions. On the other hand, the challenges found are the challenges of public opinion, the lack of optimal tools for multicultural dialogue, the decline of political support, the conﬂict among Muslims, the lack of professionalism, and the secularism. Regarding these conditions, some of the Islamic revivalism movements adapted themselves to adjust political developments in Indonesia.